Approaches to 'markets': the development of Shanghai as an international financial centre - Lai, Karen P.Y. (2007)
This thesis opens up the black box of ‘markets’ by scrutinising the process of market formation and examining its complexities in the context of Shanghai’s development as an international financial centre. The financial markets in Shanghai are framed, understood and acted upon differently by the Chinese local and central governments, regulatory institutions, local and foreign financial institutions and transnational interests. The construction of a financial centre in Shanghai is thus not only an outcome of its own historical context and development trajectory but also intrinsically bound up with the interests and decisions of other agencies acting across spatial scales and negotiated amidst conflicts of interests and power struggles. Based on empirical research that includes field observations of financial markets development in Shanghai, archival research and personal interviews conducted with local and foreign financial institutions, and Chinese government and regulatory officials in Shanghai (with some conducted in London), this study focuses on the banking sector, the securities market and strategies of foreign banks as they negotiate between the local regulatory environment and market conditions and the wider context of their global operations and strategies. I examine the relationship between state institutions and global finance capital in Shanghai and tease out how these different ‘framings’ of markets are played out in Shanghai. In doing so, I critically engage with the concept of ‘markets’ and ‘from-plan-to-market’ economy to expose its multiple identities and conceptualisations and the contested nature of the ‘marketisation’ process. I also analyse the factors contributing to Shanghai’s success, identify future challenges and highlight the complementary roles played by Shanghai as a ‘business and commercial centre’, Beijing as a ‘political centre’ and Hong Kong as an ‘offshore financial centre’.